Measuring photodarkening from Ytterbium-doped fiber amplifier at 1064 nm wavelength emission - Li, Nanxi (2013)
In this paper, photodarkening effect in Ytterbium doped fiber (YDF) amplifier is experimentally investigated and analyzed. The experimental measurement on such effect is conducted on an YDF amplifier at 1064 nm wavelength emission, under both saturated and unsaturated operational regimes. Our results demonstrate that saturated operation created by higher stimulating power level is favored to mitigate the photodarkening effect as well as to enhance the amplifier's long term reliability. Such phenomenon is explained in terms of population inversion level of Ytterbium ion doped in fiber.